PEMBATALAN AKTA WASIAT SEBAGAI AKIBAT PERBUATAN MELAWAN HUKUM YANG DILAKUKAN NOTARIS (STUDI KASUS PUTUSAN MA NO. 3124 K/ PDT/ 2013 ANTARA PENGGUGAT DM VS TERGUGAT NOTARIS LSN) - DEBORA CLAUDIA PANJAITAN (PREMISE LAW JURNAL, 2016)
A notary is a public official who is given the authority by the state tu draw up authentic deeds. He has to make them properly and correctly. If one feels the he is harmed by the deed, he can file a complaint against the Notary for not making it right as in drawing up a will. The research used juducial normative and descripstive analytic method by collecting primary and secondary data carefully. A deed can be legally null and void or revoked by court’s verdict when its material an formal requirements are not fulfilled. When it is revoked by court’s verdict, it will not have any legal force, and when it is revoked by the parties concerned it will become an underhanded deed. If a Notary makes a mistake in drawing up a deed, civil, criminal, administrative, or code of ethnics can be imposed upon him. Keywords: Revocation of Deed, Illegal Act, Notary’s Liability